DISCOURSE MARKERS IN ABSTRACTS OF INTERNATIONAL JOURNALS - Nurlaela Rahayati; Rina Herlina (Journal of English Education Program (JEEP), 2021)
This study investigated discourse markers used in international journal’ abstracts. This study was aimed at finding out: a) discourse markers used in abstracts of international journals, and b) the most dominant types of discourse markers used in international journal’ abstracts. The study employed six abstracts of international journals chosen randomly as the sample of the study. The study utilizes qualitative descriptive design. In data analysis, this study used Fraser’s theory (1999) that emphasized on four types, namely contrastive marker, elaborative marker, inferential marker, and temporal marker. In addition, the result shows that there are four types of discourse markers found in international journal’s abstracts. Elaborative marker are the most dominant types; marker and is the overuse in the abstracts. It occurred 56 times of the total six abstracts of international journals followed by 2 times for marker also, moreover, in addition, therefore, then, thus, so, or, then, 1 time for marker in addition, furthermore, for instance, beside, although, in contrast, in spite of, whereas, however, nonetheless, result indicate that, in conclusion, the result of, because, and  finally. Moreover, the study found contrastive markers consistsed of although, in contrast, in spite of, whereas, however, and nonetheless. Elaborative markers consist of and, or, in addition, furthermore, for instance, beside, and moreover. Inferential markers consist of so, therefore, thus, then, result   indicate that, the result of, in conclusion, and because. Temporal markers consist of finally. This study concludes that the most dominant types of discourse markers was elaborative markers due to the excessive use in the 6 abstracts. Keywords: abstract, discourse analysis, discourse markers, journal